2023
DOI: 10.3389/fendo.2023.1188297
|View full text |Cite
|
Sign up to set email alerts
|

The effects and underlying mechanism of extracorporeal shockwave therapy on fracture healing

Fuxian Lv,
Zhenlan Li,
Yuling Jing
et al.

Abstract: The clinical efficacy of ESWT in treating bone non union has been widely recognized, but the biological mechanism of ESWT promoting bone non union healing is still unclear. ESWT can make old callus micro fracture through mechanical conduction, form subperiosteal hematoma, promote the release of bioactive factors, reactivate the fracture healing mechanism, rebalance the activities of osteoblasts and osteoclast, promote the angiogenesis of fracture site, and accelerate the healing of bone nonunion.Over recent ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…It has been suggested that shock waves act through a mechanotransduction mechanism by inducing bone tissue reaction ( Hsu et al, 2003 ). Moreover, a recent report introduced the growth factors induced by shock waves during osteogenic differentiation of MSCs to be involved in the process of sensing and responding to the biological effects of shock waves ( Lv et al, 2023 ). The current approach, which is based on a specifically designed technical setup, MSCs differentiating toward the osteogenic lineage together with a systematic testing of conditions for SWA, offers a solid working model to address this question in the future.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that shock waves act through a mechanotransduction mechanism by inducing bone tissue reaction ( Hsu et al, 2003 ). Moreover, a recent report introduced the growth factors induced by shock waves during osteogenic differentiation of MSCs to be involved in the process of sensing and responding to the biological effects of shock waves ( Lv et al, 2023 ). The current approach, which is based on a specifically designed technical setup, MSCs differentiating toward the osteogenic lineage together with a systematic testing of conditions for SWA, offers a solid working model to address this question in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Extracorporeal shock wave therapy (ESWT) applied though single pressure waves of approximately 300 bar activates mechanotransduction ( 48 ) and thereby (re-) activates fracture healing via the release of growth factors, such as BMPs, TGF-β, and VEGF ( 49 ). Shock waves are generated by electrohydraulic, piezoelectric, or electromagnetic mechanisms ( 50 ).…”
Section: Mechanical Stimulationmentioning
confidence: 99%
“…Its mechanical actions include influencing various cellular structures such as mitochondria, endoplasmic reticulum, and intracellular vesicles, as well as enzymatic processes. The cumulative effect of these responses results in an enhancement of the overall healing process [ 12 ]. ESWT plays a crucial role in loosening adhesive tissues, expediting skeletal muscle injury recovery, and mitigating internal inflammation, resulting in a pronounced analgesic effect.…”
Section: Introductionmentioning
confidence: 99%